Standar Budaya Kerja Berbasis Kearifan Lokal Tri Hita Karana bagi Lembaga Perkreditan Desa di Bali - Ni Made Widnyani; Ni Luh Putu Surya Astitiani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
In Bali there are several institutions formed based on cultural values, traditions, and customs, one of which is the Village Credit Institution (LPD). As an institution that must always be based on the teachings of Tri Hita Karana, LPD must be able to translate these teachings and values into organizational governance and management. On the other hand, there are challenges of the times in the form of shifts and changes to the values and teachings of local wisdom, including Tri Hita Karana. Based on these problems, it is necessary to conduct research on the standard of work culture based on local wisdom Tri Hita Karana for LPDs in Bali. This research is important to do to answer the challenges faced by LPD in facing competition and changing times. Research on the standard of creating a work culture based on local wisdom Tri Hita Karana for Village Credit Institutions in Bali is using a qualitative descriptive method with a case study approach. the results of this study formed the work culture standards designed in this study, namely LPD standards in general, employee recruitment standards, employee work behavior standards, meeting ethical standards, promotion standards, and hygiene standards.